1998
DOI: 10.1063/1.368049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quenched disorder on La-modified lead zirconate titanate: Long- and short-range ordered structurally incommensurate phases, and glassy polar clusters

Abstract: Structure–property relationship studies have been performed in the La-modified lead zirconate titanate (PLZT) solution as a function of quenched La impurity content and Zr/Ti ratio by transmission electron microscopy, lattice imaging, and dielectric spectroscopy. Investigations were performed for 65/35⩽Zr/Ti⩽90/10. These investigations have demonstrated a general trend in domain structure and polar order with increasing quenched impurity concentration. For Zr/Ti ratios of 90/10 and 85/15, a structurally incomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
66
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 67 publications
6
66
0
Order By: Relevance
“…6,7 The hot-stage in situ TEM observations revealed that the modulation wavelength increases continuously with increasing temperature. Based on these studies, Viehland et al 8 suggested that the competing ferroelectric and antiferroelectric ordering in these perovskites are responsible for the presence of incommensurate modulations. However, unambiguous evidence has yet to be found.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…6,7 The hot-stage in situ TEM observations revealed that the modulation wavelength increases continuously with increasing temperature. Based on these studies, Viehland et al 8 suggested that the competing ferroelectric and antiferroelectric ordering in these perovskites are responsible for the presence of incommensurate modulations. However, unambiguous evidence has yet to be found.…”
mentioning
confidence: 99%
“…In the PLZT system, the modulation wavelength was observed to increase with Ti molar fraction. 8 Utilizing temperature as the controlled variable in the study of such transformations allows in situ TEM studies, where the evolution of the satellite reflections can be directly observed. 6,7 The hot-stage in situ TEM observations revealed that the modulation wavelength increases continuously with increasing temperature.…”
mentioning
confidence: 99%
See 3 more Smart Citations